Upaya Mengatasi Perilaku Bullying Pada Anak Melalui Edukasi Dengan Metode Intervensi Level Mikro (Casework) - Eldinda Faridzi Rachmayani Sinulingga; Erni Asneli Asbi (Yayasan Literasi Sains Indonesia, 2022)
Nowdays, social life consists of several phases and levels. As time goes by, individuals begin to interact with their peers because humans keeps growing and developing. Basicly, shifting the unfavorable behavior in teenagers is very difficult, especially when the efforts made to overcome it are not optimal. This can result in teenagers starting to show pathological symptoms, such as juvenile deliquency, motorcycle gangs, brawls between schools, and other bad behaviors, one of which is bullying. bullying acts also occurs in children from the Al Jamiyatul Washliyah Orphanage in Pulo Brayan Medan. Therefore, the purpose of this field Work Practice (Praktik Kerja Lapangan) is to provide assistance to bullying perpetrators, which is implemented in the ‘mini project’ activity using the general casework method, namely Engagement Intake Contract, Asessessment, Planning, Intervention, Evaluation, and Termination. In the process of providing assistance to clients to make them aware of the harm that bullying impacted. The results found on this program have been achieved, since the client is much better in terms of behavioral acts. This program is also beneficial for not only clients, but also for other children.